EMA/CO Combination Chemotheraphy in Gestational Trophoblastic Neoplasia: Update of Our Results - Tolga Taşçı; Işın Üreyen; Günsu Kimyon; Alper Karalök; Sevgi Koç; M. Faruk Köse; Gökhan Tulunay; Taner Turan (Medical Network, 2016)
OBJECTIVE: In this study, we aimed updating our experience about the treatment success of EMA-CO (etoposide, methotrexate, actinomycin-D, cyclophosphamide, vincristine) chemotherapy in high-risk gestational trophoblastic neoplasia (GTN). MATERIAL AND METHOD: Patients were scored according to FIGO's modified WHO system. Risk scoring of patients before 2000 was remade by using this system. Thirty-nine patients who were treated with EMA-CO between 1992 and 2013 because of high risk GTN or the resistance to single agent methotrexate and MAC III chemotherapy combinations were evaluated retrospectively. Adjuvant surgery and radiotherapy were used in selected patients. Response and effects of the prognostic factors to the response rate were analyzed. RESULTS: Median follow-up time of the patients was 74.8 months (range, 1-203). Complete clinical response was obtained in 36 (92.3%) patients with only EMA-CO or EMA-CO and surgery. The response rate of treatment was 91.3% (n:21/23) in patients taking primary EMA-CO, 93.8% (n:15/16) in patients taking secondary EMA/CO chemotherapy. Resistance to the EMA-CO treatment developed in 6 (15.3%) patients and 3 of the patients with drug resistance died. During the follow-up time disease recurred in 3 (7.7%) patients. When the antecedent pregnancy was term pregnancy or the histopathological diagnosis was choriocarcinoma or when there was liver metastasis, the treatment success decreased. The effects of tumor dimension and the presence of metastasis tended to be statistically significant in determining the resistance to therapy. CONCLUSION: EMA-CO regimen is highly effective for treatment of high-risk GTN. Because of the differences in many studies, risk factors for predicting the success of the treatment are not clear.